Progress and challenges in directing the differentiation of human iPSCs into spinal motor neurons - Castillo Bautista, Cristina Marisol; Sterneckert, Jared (Frontiers in Cell and Developmental Biology, 2023)
Motor neuron (MN) diseases, including amyotrophic lateral sclerosis, progressive bulbar palsy, primary lateral sclerosis and spinal muscular atrophy, cause progressive paralysis and, in many cases, death. A better understanding of the molecular mechanisms of pathogenesis is urgently needed to identify more effective therapies. However, studying MNs has been extremely difficult because they are inaccessible in the spinal cord. Induced pluripotent stem cells (iPSCs) can generate a theoretically limitless number of MNs from a specific patient, making them powerful tools for studying MN diseases. However, to reach their potential, iPSCs need to be directed to efficiently differentiate into functional MNs. Here, we review the reported differentiation protocols for spinal MNs, including induction with small molecules, expression of lineage-specific transcription factors, 2-dimensional and 3-dimensional cultures, as well as the implementation of microfluidics devices and co-cultures with other cell types, including skeletal muscle. We will summarize the advantages and disadvantages of each strategy. In addition, we will provide insights into how to address some of the remaining challenges, including reproducibly obtaining mature and aged MNs.